Pengaruh Venue dan Design Layout terhadap Keputusan Pembelian Jasa pada CV Muda Art Project Event Organizer - Yanti, Desi; Mariani Saragih, Agus (Civiliza Publishing, 2025)
Venue is a place where an event or activity takes place, which has various facilities and physical characteristics that can influence consumer decisions. Layout design is determining the layout design for certain elements in the venue so that it produces attractive and functional visuals. This research aims to find out whether there is an influence of venue and layout design on the decision to purchase event services at CV Muda Art Project Event Organizer. This research is a type of associative research that uses quantitative data. The research sample consisted of 61 people, namely CV Muda Art Project clients from 2017 to 2024. The data analysis technique used was multiple linear regression with partial hypothesis testing (t test), simultaneous test (F test), and coefficient of determination. The results of this research show that the venue has a positive and partially insignificant influence according to the obtained t-value of (1,709) while the layout design has a positive and significant influence on the decision to purchase services with the obtained t-value of (3,392). Simultaneously the venue and layout design have a significant influence on the decision to purchase services at CV Muda Art Project Event Organizer as evidenced by the F-calculation value of (20,658) and a determination coefficient (R square) of (41.6%), with the remaining (58.4%) explained by other variables not examined.